Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fnins.2018.00936
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Microstructural Changes of the Blood-Nerve Barrier in Peripheral Neuropathy

Abstract: Peripheral neuropathy is accompanied by changes in the neuronal environment. The blood-nerve barrier (BNB) is crucial in protecting the neural homeostasis: Tight junctions (TJ) seal paracellular spaces and thus prevent external stimuli from entering. In different models of neuropathic pain, the BNB is impaired, thus contributing to local damage, immune cell invasion and, ultimately, the development of neuropathy with its symptoms. In this study, we examined changes in expression and microstructural localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…Next, we chose to further examine the well-standardized mononeuropathy CCI in mice, characterized also by an inflammatory reaction due to the ligatures around the SN. Previous data from our and other labs revealed that CCI caused claudin-1, claudin-5, occludin and ZO-1 downregulation in the SN (Moreau et al, 2016;Reinhold et al, 2018;Reinhold et al, 2019). In WT mice, claudin-12-IR was found in myelinating, MBP-positive Schwann cells and S100b-positive Schwann cells (Fig 2A).…”
Section: Claudin-12 and Claudin-19 Loss After Nerve Injurysupporting
confidence: 51%
See 4 more Smart Citations
“…Next, we chose to further examine the well-standardized mononeuropathy CCI in mice, characterized also by an inflammatory reaction due to the ligatures around the SN. Previous data from our and other labs revealed that CCI caused claudin-1, claudin-5, occludin and ZO-1 downregulation in the SN (Moreau et al, 2016;Reinhold et al, 2018;Reinhold et al, 2019). In WT mice, claudin-12-IR was found in myelinating, MBP-positive Schwann cells and S100b-positive Schwann cells (Fig 2A).…”
Section: Claudin-12 and Claudin-19 Loss After Nerve Injurysupporting
confidence: 51%
“…Deletion of Cldn12 gene via KO or siRNA in the SN led to mechanical allodynia. Although nerve injury drives loss of tight junction protein expression and barrier opening in the PNS and spinal cord (4,5,13,51), it is unknown whether this is sufficient to cause pain. Indeed, barrier opening by tissue plasminogen activator (4), by siRNA or peptides against Cldn1 opens the perineurial barrier without causing hypersensitivity (6,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations